The Function of the State Revenue and Expenditure Budget Stabilizer in Supporting Development - Cahya F, Randi Dwi; Arkan; Hamimi S, Thoriq; Reza Rahardian P, Muhammad; Muksin, Ahmad (Yayasan Mentari Madani, 2024)
This research discusses the stabilizing function of the State Budget (APBN) in supporting economic development in Indonesia. The state budget not only acts as a tool for government financial management, but also as a major instrument in encouraging economic growth and achieving national development goals. In fluctuating economic situations, the state budget is used as a stabilization instrument through adaptive fiscal policy. For example, increased public spending or tax cuts during a recession to boost economic growth and reduce unemployment, as well as austerity measures when the economy is overheating to prevent inflation. In addition, the state budget contributes to creating a stable investment climate and supporting long-term economic growth through strategic allocation of funds, such as investment in infrastructure, education, and research and development. The stabilizing function of the state budget is also closely linked to the government's efforts to achieve sustainable development goals, including the reduction of social inequality, increased access to basic services, and environmental sustainability. This study aims to analyze the concept and working mechanism of the state budget stabilizer, explore the fiscal policies applied to respond to different economic conditions, and understand how the allocation of state budget funds supports long-term economic development and sustainable development goals. Through prudent and balanced fiscal policy, the state budget can play a significant role in promoting inclusive, sustainable and stable economic growth